Harry Potter and the goblet of fire - Rowling, J.K. (New York : Scholastic, 2000)
Juvenile fiction.
Sequel to Harry Potter and the prisoner of Azkaban.
Keywords: England -- Juvenile fiction; Hogwarts school of witchcraft and wizardry (Imaginary place) -- Juvenile fiction; Magic -- Juvenile fiction; Schools -- Juvenile fiction